INCOME AND VALUE-ADDED ANALYSIS OF COW'S MILK-PROCESSED IN CIBUNGBULANG SUBDISTRICT, BOGOR - Elpawati Elpawati; Nabilah Nurshalihah; Dewi Rohma Wati (AGRIBUSINESS JOURNAL, 2022)
This study aims to determine the operating income and added value of processed cow's milk products in the agro-industry of the Cibungbulang Dairy Farming Business Area (KUNAK), Bogor. The location used was selected purposively, namely Papajo and Etzel agroindustry in Cibungbulang District. The sample population consists of business owners and employees, who served as respondents. Data was collected using a list of questions or questionnaires to obtain information, followed by analysis using Microsoft Excel. Subsequently, the income and R/C ratio were calculated, while the Hayami method was used to determine the added value of each product. The results showed that the incomes for yogurt, kefir, and ice cream were IDR29,973,500/month, IDR13,648,334/month, and IDR39,204,167/month, respectively. The R/C ratio of yogurt was 1.4 > 1, kefir 1.6 > 1, and ice cream 3.1 > 1, which indicates that the cow's milk processing business is profitable and feasible. The added value of yogurt, kefir, and ice cream products was IDR14,291/liter, IDR5,619/liter, and IDR 53,900/liter with value-added ratios of 44.66%, 23.41%, and 74.86%, respectively.